Headwinds of COVID-19 and India's Inward Remittances - Soumasree Tewari; Ranjeeta Mishra (RBI Bulletin, 2022)
Notwithstanding headwinds of COVID-19, India's inward remittances have proven to be a resilient source of current account receipts. In this article cross-country remittances inflows are found to be driven by altruism motive, captured by the infection rate in the destination country and the stringency of the lockdown in the source countries. The fifth round of the survey on remittances for the reference period 2020-21 finds that the share of Gulf countries has declined, reflecting slower pace of migration and presence of Indian diaspora in informal sectors which was hit the most during the pandemic period. Further, the impact of COVID-19 led stressed income conditions was discernible as small size transactions gained share in total remittances in 2020-21. The divergence was also reflected in the bank-group wise transactions as public sector banks lost market share while private banks retained their dominance in remittances business.
Keywords: 330; Remittance; India